Process for preparing silver nanoparticles of less than 200 nm by microemulsion

CN122683130BActive Publication Date: 2026-10-20HA SHEN TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611170570.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-20
Estimated Expiration
2046-08-04

AI Technical Summary

Technical Problem

[0005]本申请的目的在于提供一种微乳液法制备200nm以下纳米银颗粒的工艺,解决现有微乳液法制备纳米银颗粒时粒径分散不均、易团聚、烧结活性低的问题,同时克服微乳液体系稳定性不足、表面包覆抑制团聚效果差的缺陷,制备出满足烧结银浆使用要求的高性能纳米银颗粒

Benefits of technology

1、本申请制备的纳米银颗粒分散性良好(粒径控制在200nm以下),有利于烧结银浆的加工成型及印刷操作,可避免印刷过程中出现堵塞、涂布不均等问题;密度较高,其中松装密度≥3g/cm3、振实密度≥4.5g/cm3,能够有效促进烧结银浆加工过程中的致密化,提升烧结后导电膜的致密度和结构稳定性;烧结活性优异,在250℃的低温条件下即可烧结形成具有良好性能的导电膜,适配烧结银浆的低温加工需求,降低加工能耗,同时避免高温加工对基材造成损伤。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122683130B_ABST
    Figure CN122683130B_ABST
Patent Text Reader

Abstract

The application discloses a process for preparing silver nanoparticles with a size of less than 200 nm by a microemulsion method, and belongs to the technical field of nanometer material preparation. The process comprises the following steps: preparing an oil phase system and a water phase system respectively, wherein the oil phase system comprises polyethylene glycol monoalkyl ether or polyethylene glycol monoalkyl acid ester oil phase with an HLB value of 8-18 and a weight average molecular weight of 100-100000, alcohol or amine surfactant, and alcohol amine or amino polyhydric alcohol reducing agent; the water phase system comprises a silver source and water. The two phases are mixed and stirred to form a emulsion, and then the emulsion is reacted at 50-80 DEG C to form an oil-in-water microemulsion microreactor, and finally, the silver nanoparticles are prepared through post-treatment. Through the cooperation of various components, a stable oil-in-water system is formed, and the prepared silver nanoparticles have good dispersity (particle size <200 nm), high density and high sintering activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of nanomaterial preparation technology, and in particular to a process for preparing silver nanoparticles below 200 nm using a microemulsion method. Background Technology

[0002] With the continuous development of third-generation wide-bandgap semiconductors, their applications in consumer electronics, smart lighting, new energy vehicles, aerospace, and military fields are becoming increasingly widespread, placing higher demands on matching packaging materials. Sintered silver paste, due to its unique characteristics of "low-temperature processing and high-temperature service," high electrical and thermal conductivity, and excellent reliability, is gradually becoming one of the mainstream packaging and interconnect materials for third-generation semiconductor devices.

[0003] Bulk silver has a melting point of 961℃, while the sintering and solidification temperature of sintered silver paste is typically controlled below 250℃. The key factor causing this significant difference lies in the silver nanoparticles. According to surface energy theory, the smaller the particle size, the greater its specific surface energy, and the higher the sintering driving force it provides, thus significantly improving sintering activity. Silver nanoparticles typically have a particle size of less than 1μm, enabling them to "melt" and sinter at temperatures far below the melting point of bulk silver, ultimately forming a dense silver film. However, small-diameter particles with high surface energy spontaneously aggregate into large-diameter particles with low surface energy, leading to a loss of sintering activity. Therefore, improving the dispersibility of silver nanoparticles and effectively inhibiting their aggregation has become a major technical challenge in the preparation process.

[0004] Microemulsion technology is a technique that uses microemulsions as nanoreactors to prepare nanomaterials. This method forms a spontaneous, thermodynamically stable system through an oil phase, an aqueous phase, and surfactants (such as short-chain alcohols), creating a nanoconfined reaction, and has become one of the key technologies for preparing nanomaterials. The key challenges in this method are: firstly, how to form a sufficiently stable microemulsion to provide a reliable confined environment for the growth of silver nanoparticles; and secondly, how to further inhibit the aggregation of silver nanoparticles through effective surface coating, thereby maintaining their high sintering activity and ultimately solving the problems of poor dispersibility and insufficient sintering activity in existing silver nanoparticle preparation methods. Summary of the Invention

[0005] The purpose of this application is to provide a microemulsion method for preparing silver nanoparticles smaller than 200 nm, solving the problems of uneven particle size dispersion, easy agglomeration, and low sintering activity in existing microemulsion methods for preparing silver nanoparticles. It also overcomes the shortcomings of insufficient stability of the microemulsion system and poor surface coating effect in inhibiting agglomeration, thus producing high-performance silver nanoparticles that meet the requirements for sintered silver paste. This application uses a suitable oil-in-water (O / W) system combined with a suitable surfactant to form a nanoreactor, preparing uniform spherical / quasi-spherical silver particles. Surface coating can be completed within the microreactor, maintaining good particle dispersibility. The technical solution provided by this application is as follows: This application provides a process for preparing silver nanoparticles smaller than 200 nm using a microemulsion method, comprising the following steps: An oil-phase system and an aqueous-phase system were prepared separately; the oil-phase system contained an oil phase, a surfactant, and a reducing agent; the aqueous-phase system contained a silver source and water. The oil phase system and the aqueous phase system are mixed and stirred until an emulsion is formed. The mixture is then reacted at 50°C to 80°C to form an oil-in-water (O / W) microemulsion. After post-processing and washing, nano-silver particles with a particle size of less than 200 nm were obtained; The oil phase is selected from at least one of polyethylene glycol monoalkyl ether and polyethylene glycol monoalkyl ester, with a hydrophilic-lipophilic balance (HLB) value of 8 to 18 and a weight-average molecular weight of 100 to 100,000. The surfactant is selected from at least one of the following: C1-C4 monohydric alcohols, C2-C4 dihydric alcohols, C3-C4 trihydric alcohols, C1-C18 monohydric primary amines, C2-C3 dihydric primary amines, C3 trihydric primary amines, C2-C6 monohydric secondary amines, and C3-C9 monohydric tertiary amines. The reducing agent is selected from at least one of alkanolamine compounds and amino polyol compounds.

[0006] In some preferred embodiments, the oil phase is selected from at least one of polyethylene glycol monododecyl ether, polyethylene glycol monohexadecyl ether, polyethylene glycol mono(Z)-9-octadecenyl ether, polyethylene glycol monooctadecyl ether, hexanol polyoxyethylene ether, octyldecyl alcohol polyoxyethylene ether, n-octyl alcohol polyoxyethylene ether, dodecyl alcohol polyoxyethylene ether, tetradecyl alcohol polyoxyethylene ether, hexadecyl alcohol polyoxyethylene ether, octadecyl alcohol polyoxyethylene ether, coconut oil polyoxyethylene ether, polyethylene glycol monododecyl ester, polyethylene glycol monotetradecyl ester, polyethylene glycol monohexadecyl ester, polyethylene glycol mono(Z)-9-octadecenyl ester, polyethylene glycol monooctadecyl ester, and polyethylene glycol coconut oil ester.

[0007] In some preferred embodiments, the oil phase is selected from at least one of dodecyl alcohol polyoxyethylene ether and octadecyl alcohol polyoxyethylene ether.

[0008] In some preferred embodiments, the volume ratio of the oil phase system to the aqueous phase system is 0.01:1 to 10:1, preferably 0.1:1 to 1:1.

[0009] In some preferred embodiments, the surfactant is selected from at least one of methanol, ethanol, propanol, butanol, ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, glycerol, 1,2,3-butanetriol, 1,2,4-butanetriol, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, n-propylamine, dipropylamine, tripropylamine, 1,2-propanediamine, 1,3-propanediamine, propylenetriamine, n-butylamine, n-pentylamine, n-hexylamine, n-heptylamine, n-octylamine, n-nonylamine, n-decylamine, n-dodecylamine, n-tetradecylamine, n-hexadecylamine, n-octadecylamine, oleic acid amine, and linoleic acid amine.

[0010] In some preferred embodiments, the surfactant is selected from at least one of n-dodecylamine and n-octadecylamine.

[0011] In some preferred embodiments, the concentration of the surfactant is 0.01 g / L to 100 g / L, preferably 0.1 g / L to 10 g / L.

[0012] In some preferred embodiments, the alkanolamine compound is selected from at least one of methanolamine, ethanolamine, propanolamine, isopropanolamine, diethanolamine, triethanolamine, diisopropanolamine, triisopropanolamine, N-methylmethanolamine, N-methylethanolamine, N,N-dimethylethanolamine, N-ethylethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, N-acetylethanolamine, N-butyldiethanolamine, N-tert-butyldiethanolamine, and N,N-dimethylisopropanolamine. The amino polyol compound is selected from at least one of 3-amino-1,2-propanediol, 2-amino-1,3-propanediol, and 4-amino-1,2-butanediol.

[0013] In some preferred embodiments, the reducing agent comprises both the alkanolamine compound and the amino polyol compound in a molar ratio of 20:1 to 100:1; wherein the alkanolamine compound is isopropanolamine; and the amino polyol compound is selected from at least one of 3-amino-1,2-propanediol and 2-amino-1,3-propanediol.

[0014] In some preferred embodiments, the reducing agent is selected from at least one of isopropanolamine, 3-amino-1,2-propanediol, and 2-amino-1,3-propanediol.

[0015] In some preferred embodiments, the molar ratio of the reducing agent to the silver source is 0.5:1 to 10:1, preferably 0.5:1 to 2:1.

[0016] In some preferred embodiments, the silver source is selected from at least one of silver nitrate, silver sulfate, silver chloride, silver oxide, silver trifluoroacetate, silver formate, silver acetate, silver oxalate, and silver carbonate; In the aqueous system, the mass ratio of silver source to water is 1:1000 to 1:1.

[0017] By adopting the above technical solution, the microemulsion method for preparing silver nanoparticles smaller than 200 nm provided in this application has the following beneficial effects: 1. The nano-silver particles prepared in this application exhibit good dispersibility (particle size controlled below 200 nm), which is beneficial for the processing, molding, and printing of sintered silver paste, and can avoid problems such as clogging and uneven coating during the printing process; the density is high, with a loose packing density ≥3 g / cm³. 3 Tap density ≥ 4.5 g / cm³ 3 It can effectively promote densification during the sintering process of silver paste, and improve the density and structural stability of the conductive film after sintering. It has excellent sintering activity and can sinter to form a conductive film with good performance at a low temperature of 250℃, which is suitable for the low temperature processing requirements of sintered silver paste, reduces processing energy consumption, and avoids damage to the substrate caused by high temperature processing.

[0018] 2. This application selects an oil-phase solvent with an HLB value in the range of 8 to 18 to form a stable oil-in-water (O / W) microemulsion system, providing a stable confined environment for the controllable growth of silver nanoparticles. Alcohols or amines with strong affinity for the silver source and high solubility in the oil or aqueous phase are selected as surfactants. These surfactants not only stabilize the microemulsion system but also have a certain lubricating effect, which can effectively prevent the formation of loose hard agglomerates between silver nanoparticles, thereby increasing the particle density. The surfactants can be removed at a relatively low temperature (e.g., 350°C) and can slowly evaporate at a sintering temperature of 250°C, effectively reducing the hindrance of surfactant residues to the sintering process and ensuring the conductivity and density of the conductive film after sintering. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1A scanning electron microscope (SEM) image of the silver nanoparticles prepared by the process in Example 1 of this application; Figure 2 This is a SEM image of the silver nanoparticles prepared by the process of Comparative Example 3 of this application. Detailed Implementation

[0021] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0022] The term "an embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of this application. In the description of this application, it should be understood that the terms "upper," "lower," "top," "bottom," etc., indicating orientation or positional relationships based on the orientation or positional relationships shown in the accompanying drawings, are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application. Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Moreover, the terms "first," "second," etc., are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments of this application described herein can be implemented in orders other than those illustrated or described herein.

[0023] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to an integer, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are included. For example, a specified range from “1 to 10” should be considered to include any and all subranges between the minimum value 1 and the maximum value 10. Exemplary subranges of the range 1 to 10 include, but are not limited to, 1 to 6.1, 3.5 to 7.8, 5.5 to 10, etc.

[0024] This application utilizes a suitable oil-in-water (O / W) system and a suitable surfactant to form a nanoreactor. The reducing agent and silver source are dispersed separately in different phases, allowing them to react within the microemulsion system to generate uniform spherical / quasi-spherical silver nanoparticles. Simultaneously, the surface coating process is completed within the microreactor, effectively inhibiting particle agglomeration and maintaining good product dispersibility. The core of this application lies in the synergistic effect of the oil phase (O), surfactant (D), catalyst, and aqueous phase (W). Through the rational combination of these components, a stable microreactor is formed, achieving efficient preparation of silver nanoparticles. The prepared silver nanoparticles possess excellent dispersibility (particle size ≤200nm) and high density (≥4.5g / cm³). 3 Its excellent properties, including high sintering activity (it can sinter at 250℃ to form a good conductive film), meet the requirements for the use of sintered silver paste.

[0025] The process for preparing silver nanoparticles smaller than 200 nm using the microemulsion method provided in this application embodiment specifically includes the following steps: I. Prepare oil-phase and aqueous-phase systems separately. The oil-phase system contains oil, surfactant, and reducing agent; the aqueous-phase system contains silver source and water. By separately supporting the reducing agent and silver source (oxidizing agent), premature contact and reaction between the two are avoided, ensuring that subsequent reactions proceed in a controllable and uniform manner. The reducing agent and surfactant are placed in the oil-phase system, where the surfactant has better solubility and can fully exert its effect; the reducing agent is stably dispersed in the oil phase, preventing premature contact with the silver source. The aqueous-phase system contains the silver source and water. The silver source has better solubility in water than in the oil phase; placing it in water ensures complete dissolution, preventing undissolved silver source from affecting reaction uniformity, thus guaranteeing the uniformity of the silver nanoparticle size.

[0026] The oil phase is selected from at least one of polyethylene glycol monoalkyl ethers and polyethylene glycol monoalkyl esters, with a hydrophilic-lipophilic balance (HLB) value of 8-18 and a weight-average molecular weight of 100-100,000. An HLB value of 8-18 is chosen to form a stable oil-in-water (O / W) system. If the HLB value is too low, the oil phase is extremely incompatible with water, easily leading to liquid stratification. If the HLB value is too high, the oil phase is overly compatible with water, resulting in oil-water miscibility and uniform dispersion of the oil phase. Neither excessively low nor excessively high HLB values ​​allow for the formation of microemulsions at the microscopic level. This oil phase exhibits excellent hydrophilic-lipophilic balance and can spontaneously form a stable oil-in-water (O / W) microemulsion system when mixed with an aqueous system, providing a confined environment for the growth of silver nanoparticles.

[0027] The surfactant is selected from at least one of C1-C4 monohydric alcohols, C2-C4 dihydric alcohols, C3-C4 trihydric alcohols, and C1-C18 primary monohydric amines, C2-C3 primary dihydric amines, C3 primary trihydric amines, C2-C6 secondary monohydric amines (e.g., dimethylamine, diethylamine, dipropylamine, etc.), and C3-C9 tertiary monohydric amines (e.g., trimethylamine, triethylamine, tripropylamine, etc.). The main function of the surfactant is to reduce the oil-water interfacial tension and promote the formation and stabilization of the microemulsion. Simultaneously, during the growth of silver nanoparticles, it can adsorb onto the particle surface, forming a steric hindrance layer that effectively inhibits particle aggregation. The reducing agent is selected from at least one of alkanolamine compounds and amino polyol compounds. The reducing agent is dispersed in the oil phase system and can undergo a controlled reduction reaction with the silver source diffused from the aqueous phase system at the oil-water interface, regulating the silver formation rate and thus controlling the nucleation and growth process of the silver nanoparticles. By placing the reducing agent and the silver source in the oil phase system and the aqueous phase system respectively, the violent and uncontrollable reaction caused by direct mixing of the two is avoided, which is conducive to achieving homogeneous nucleation and slow, uniform growth of silver nanoparticles.

[0028] II. Microemulsion Reaction: The oil phase system and aqueous phase system are mixed and stirred until an emulsion state is reached. The mixture is then reacted at 50℃~80℃ to form an oil-in-water (O / W) microemulsion. It should be noted that if the reaction temperature exceeds 80℃, the microemulsion system will lose stability and transform into a homogeneous liquid. Its particle growth mechanism will also change to a seed-induced aggregation and growth mode, which is not conducive to obtaining small-sized silver nanoparticles with uniform particle size. In a stable microemulsion system, the oil phase is encapsulated by surfactants to form nanoscale oil droplets, uniformly dispersed in the continuous aqueous phase. Silver atoms diffuse from the aqueous phase to the oil-water interface, undergo a reduction reaction with the reducing agent in the oil phase system, and are reduced to silver atoms, which then nucleate and grow into silver nanoparticles. In this process, a synergistic effect is formed between the oil phase, surfactant, and reducing agent: the oil phase provides a stable confined environment; the surfactant regulates interfacial properties and forms a coating layer on the particle surface to inhibit aggregation; and the reducing agent controls the reaction rate to ensure uniform particle growth. The reasonable combination of the three elements enables the microreactor to maintain high stability during the reaction process, allowing the silver nanoparticles to grow controllably within the confined space. Ultimately, silver nanoparticles with a particle size of less than 200 nm and a spherical or near-spherical morphology are obtained, with good dispersion between particles and no obvious agglomeration.

[0029] III. Post-treatment and washing: After the reaction is complete, post-treatment and washing are performed to remove unreacted raw materials, residual surfactants, and byproducts, yielding pure silver nanoparticles. The washed silver nanoparticles retain an appropriate coating layer on their surface, exhibiting good redispersibility and anti-aggregation ability. They also maintain high sintering activity after drying, facilitating the subsequent preparation of sintered silver paste.

[0030] In some preferred embodiments, the oil phase is selected from at least one of polyethylene glycol mono-dodecyl ether, polyethylene glycol mono-hexadecyl ether, polyethylene glycol mono(Z)-9-octadecenyl ether, polyethylene glycol mono-octadecyl ether, hexanol polyoxyethylene ether, octadecanol polyoxyethylene ether, n-octyl alcohol polyoxyethylene ether, dodecyl alcohol polyoxyethylene ether, tetradecyl alcohol polyoxyethylene ether, hexadecyl alcohol polyoxyethylene ether, octadecyl alcohol polyoxyethylene ether, coconut oil polyoxyethylene ether, polyethylene glycol mono-dodecyl ester, polyethylene glycol mono-tetradecyl ester, polyethylene glycol mono-hexadecyl ester, polyethylene glycol mono(Z)-9-octadecenyl ester, polyethylene glycol mono-octadecyl ester, and polyethylene glycol cocoate. Among these, polyethylene glycol monoalkyl ether oil phases exhibit good hydrophilic-lipophilic balance, maintaining the stability of the microemulsion system over a wide temperature range. Furthermore, the ether bond structure in their molecular chains demonstrates good tolerance to weakly acidic to neutral environments, is not prone to hydrolysis, and is beneficial for maintaining the structural integrity of the microreactor over the long term. The polyethylene glycol monoalkyl ester oil phase also exhibits a certain degree of chemical stability, which is closely related to the pH value of the system. Experimental measurements show that the pH value of the solution after mixing in this application is approximately 5-7, indicating a weakly acidic environment. Under these conditions, the ester structure can withstand the reaction without significant hydrolysis. Furthermore, the amine surfactants contained in the system can accept excess protons (H+). + By appropriately increasing the pH value of the solution, the ester structure can be further protected, the chemical stability of the oil phase can be maintained, and the stable operation of the microemulsion system can be ensured during the reaction process.

[0031] Preferably, the oil phase is selected from at least one of dodecyl alcohol polyoxyethylene ether and octadecyl alcohol polyoxyethylene ether. Dodecyl alcohol polyoxyethylene ether has a moderate carbon chain length and hydrophilic-lipophilic balance, enabling it to rapidly form a stable microemulsion system under conventional stirring conditions. Its long molecular chain facilitates synergistic arrangement with surfactants, forming a stable interfacial film at the oil-water interface, thus providing a size-controllable confined reaction environment for the nucleation and growth of silver nanoparticles. Octadecyl alcohol polyoxyethylene ether has an even longer carbon chain and stronger hydrophobicity, resulting in microemulsion droplets with higher structural stability. Furthermore, its long-chain structure creates a more significant steric hindrance effect on the particle surface, effectively inhibiting the aggregation of silver nanoparticles. Both have good compatibility with the amine surfactants and alkanolamine reducing agents selected in the system, ensuring long-term stability of the microemulsion at reaction temperatures of 50℃~80℃ and facilitating the acquisition of well-dispersed spherical or near-spherical silver nanoparticles with a particle size of less than 200nm. Therefore, dodecyl alcohol polyoxyethylene ether and octadecyl alcohol polyoxyethylene ether are the preferred oil phases in this application. The two oil phases can be used alone or in combination, and there are no restrictions on the specific method.

[0032] In some preferred embodiments, the volume ratio of the oil phase system to the aqueous phase system is 0.01:1 to 10:1, and preferably, the volume ratio is 0.1:1 to 1:1. If the volume ratio is too low, the total oil / water interface area is insufficient, reducing the contact reaction efficiency between silver ions and the reducing agent. Simultaneously, since the reducing agent is mainly present in the oil phase, insufficient oil phase results in an inadequate absolute content of the reducing agent relative to the silver ions, failing to fully reduce the silver ions. If the volume ratio is too high, excessive oil phase may increase the system viscosity, affecting the stability of the microemulsion and making it prone to O / W to W / O phase transformation or emulsion aggregation, thus disrupting the confined reaction space, causing uncontrolled particle growth, and resulting in problems such as increased particle size, irregular morphology, and severe agglomeration.

[0033] In some preferred embodiments, the surfactant is selected from at least one of methanol, ethanol, propanol, butanol, ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, glycerol, 1,2,3-butanetriol, 1,2,4-butanetriol, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, n-propylamine, dipropylamine, tripropylamine, 1,2-propanediamine, 1,3-propanediamine, propylenetriamine, n-butylamine, n-pentylamine, n-hexylamine, n-heptylamine, n-octylamine, n-nonylamine, n-decylamine, n-dodecylamine, n-tetradecylamine, n-hexadecylamine, n-octadecylamine, oleic acid amine, and linoleic acid amine. This application selects C1-C4 monohydric alcohols, C2-C4 dihydric alcohols, C3-C4 trihydric alcohols, and C1-C18 primary monohydric amines, C2-C3 primary dihydric amines, C3 primary trihydric amines, C2-C6 secondary monohydric amines (e.g., dimethylamine, diethylamine, dipropylamine, etc.), and C3-C9 tertiary monohydric amines (e.g., trimethylamine, triethylamine, tripropylamine, etc.) as surfactants. All of these are beneficial for adjusting the droplet size of microemulsions (mainly by increasing the number of microemulsion droplets and reducing their volume). Amines can also stabilize the structure of ester oil phases by accepting excess protons in the system. It should be noted that methanol has no obvious reducing properties under the reaction temperature and weakly acidic conditions of this system, and is also suitable as a surfactant. Long-chain alcohols (≥5 carbon atoms) are similar in structure to polyethylene glycol derivatives in the oil phase, making them prone to free migration in the oil phase. This leads to a decrease in the integrity and stability of the microemulsion interfacial film, resulting in abnormal growth of silver particles and failing to meet the particle size control requirements below 200 nm required in this application. Although long-chain amines also have long-chain structures, they can undergo protonation and become positively charged under the weakly acidic environment of this system. This enhances the electrostatic repulsion between microemulsion droplets, improving system stability, while the presence of the charge limits their free migration ability in the oil phase. Therefore, they are suitable for this application. Although short-chain alcohols and short-chain amines exhibit some migration at the interface due to their small molecular size, their impact on the integrity of the interfacial film is limited. Furthermore, the long-chain molecules of the oil phase and the short-chain surfactants form long bundles and short-wedge mixed structures of short-chain alcohols / short-chain amines, which can enhance the mechanical strength and stability of the interfacial film. Therefore, they are suitable for this application.

[0034] Preferably, the surfactant is selected from at least one of n-dodecylamine and n-octadecylamine. n-Dodecylamine has a moderate carbon chain length, which is well-matched with the preferred oil phase (dodecyl alcohol polyoxyethylene ether), allowing it to form a dense adsorption layer at the oil-water interface. Simultaneously, under weakly acidic conditions, partial protonation generates electrostatic repulsion, inhibiting microemulsion droplet aggregation. n-Octadecylamine has a longer carbon chain, stronger hydrophobicity, more robust interfacial adsorption, and a more significant steric hindrance effect, thus more effectively inhibiting the aggregation of silver nanoparticles. Both surfactants exhibit good compatibility with the oil phase and reducing agent in the system, which is beneficial for obtaining silver nanoparticles with a particle size of less than 200 nm and good dispersibility; therefore, they are the preferred surfactants in this application.

[0035] In some preferred embodiments, the concentration of the surfactant is 0.01 g / L to 100 g / L, preferably 0.1 g / L to 10 g / L. If the concentration is too low, the surfactant is insufficient to cover the oil-water interface, making it difficult to form sufficiently small and stable microemulsion droplets, which can easily lead to an increase in the particle size of the silver nanoparticles or aggregation. If the concentration is too high, excessive surfactant will disrupt the ordered structure of the interface, thereby reducing the stability of the microemulsion, or even triggering side reactions or increasing the difficulty of subsequent washing.

[0036] In some preferred embodiments, the amine compounds are selected from at least one of methanolamine, ethanolamine, propanolamine, isopropanolamine, diethanolamine, triethanolamine, diisopropanolamine, triisopropanolamine, N-methylmethanolamine, N-methylethanolamine, N,N-dimethylethanolamine, N-ethylethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, N-acetylethanolamine, N-butyldiethanolamine, N-tert-butyldiethanolamine, and N,N-dimethylisopropanolamine; the amino polyol compounds are selected from at least one of 3-amino-1,2-propanediol, 2-amino-1,3-propanediol, and 4-amino-1,2-butanediol. The above-mentioned reducing agent components are mainly short-chain amino alcohols or amines, in which the amino and hydroxyl groups are located close to each other, easily forming intramolecular hydrogen bonds, thereby changing the electron cloud distribution on the nitrogen atom, making its lone pair electrons more readily reduce silver ions. It should be noted that under weakly acidic conditions (pH 5-7), the nitrogen atom readily captures protons (H+). +Therefore, this application uses sterically hindered amine compounds (such as isopropanolamine, diethanolamine, etc., containing secondary or tertiary amine structures) as the main reducing agent (in larger quantities). Their steric hindrance structure can slow down the proton capture rate and maintain the reducing ability. At the same time, a small amount of amino alcohols that easily capture protons are used as secondary reducing agents or proton capture agents (in smaller quantities). The two work synergistically to ensure the continuous progress of the reduction reaction. If the pH value of the system is adjusted with alkaline conditions, protonation can be inhibited, but it will cause some ester oil phases to saponify and transform into a homogeneous phase. At the same time, the sphericity of the obtained silver nanoparticles is poor. It should be noted that the above proton capture is actually a dynamic equilibrium process. The distinction between the main reducing agent and the secondary reducing agent is mainly based on their functional emphasis in the system, and is not an absolute boundary.

[0037] Preferably, the reducing agent comprises both an alkanolamine compound and an amino polyol compound in a molar ratio of 20:1 to 100:1. The alkanolamine compound is isopropanolamine, whose secondary amine structure possesses both suitable reducing properties and steric hindrance, making it suitable as the primary reducing agent. The amino polyol compound is selected from at least one of 3-amino-1,2-propanediol and 2-amino-1,3-propanediol; its molecule has an amino group adjacent to multiple hydroxyl groups, exhibiting strong proton-trapping ability, making it suitable as a secondary reducing agent. Within this molar ratio range, the proportion of primary and secondary reducing agents is appropriate, ensuring sufficient reduction driving force while avoiding excessive secondary reducing agent leading to overly rapid reduction and particle growth.

[0038] Preferably, the reducing agent is directly selected from at least one of isopropanolamine, 3-amino-1,2-propanediol, and 2-amino-1,3-propanediol. This is because isopropanolamine has a moderate steric hindrance effect, maintaining good reducing activity under weakly acidic conditions while avoiding excessive protonation and deactivation, making it suitable as the main reducing agent to stably control the reaction rate. 3-amino-1,2-propanediol and 2-amino-1,3-propanediol are amino polyols, with amino groups adjacent to multiple hydroxyl groups in their molecules, exhibiting strong proton-scavenging ability, making them suitable as secondary reducing agents or proton scavengers, helping to maintain pH stability and ensure the continuous progress of the reduction reaction. These three reducing agents can be used individually or in combination, resulting in a simple formulation, wide availability of raw materials, and ease of process scale-up and batch stability control. They also avoid the side reaction risks and subsequent washing burden caused by introducing too many components, thus constituting a more preferred embodiment of this application.

[0039] In some preferred embodiments, the molar ratio of reducing agent to silver source is 0.5:1 to 10:1, and preferably, the molar ratio is 0.5:1 to 2:1. The lower limit of this ratio is set at 0.5:1, mainly based on the following considerations: the reducing agent needs to be slightly in excess of the stoichiometric ratio (Ag... +The theoretical molar ratio for reduction to Ag is 1:1. Since some alkanolamine compounds may be oxidized by dissolved oxygen in the aqueous phase or protonated and lose their reducing activity, an appropriate excess can ensure sufficient reduction of silver ions. The upper limit of this ratio is set at 10:1, mainly due to the solubility of the reducing agent in the oil phase system and the phase structure stability of the microemulsion system. Excessive reducing agent may cause the oil phase system to become saturated, destroy the water-in-oil microemulsion structure, and induce a transformation to a bicontinuous phase or water-in-oil type. At the same time, an excessively high proportion of reducing agent may also cause a decrease in raw material utilization and an increase in the burden of subsequent purification.

[0040] In some preferred embodiments, the silver source is selected from at least one of silver nitrate, silver sulfate, silver chloride, silver oxide, silver trifluoroacetate, silver formate, silver acetate, silver oxalate, and silver carbonate.

[0041] All of the aforementioned silver sources can provide free silver ions to participate in the reduction reaction. Among them, silver nitrate is the preferred silver source in this application because of its good water solubility, high degree of dissociation, lack of coordination interference from anions, and ease of purification, which ensures efficient mass transfer and uniform distribution of silver ions in the microemulsion system. It should be noted that when a silver source with poor water solubility (such as silver chloride, silver oxide, silver carbonate, etc.) is selected, the silver source is not completely dissolved in the aqueous phase, but is dispersed in the water in the form of solid particles, forming a solid-liquid suspension. After this suspension is mixed with the oil phase system, a composite reaction system is formed in which a solid-liquid dispersion and a liquid-liquid microemulsion coexist.

[0042] In the aqueous system, the mass ratio of silver source to water is 1:1000 to 1:1. For silver sources with different solubilities, the supply rate of silver ions can be controlled by selecting an appropriate mass ratio within this range, thereby controlling the nucleation and growth process of silver nanoparticles to obtain silver nanoparticles with a particle size of less than 200 nm and good dispersibility.

[0043] The following detailed description of examples of this application is exemplary and used only to explain this application, and should not be construed as limiting this application. The raw materials used are shown in Table 1: Table 1

[0044] Example 1 A process for preparing silver nanoparticles smaller than 200 nm using a microemulsion method includes the following steps: 1. Preparation of the oil phase system: Add 60g of octadecyl alcohol polyoxyethylene ether, 80g of isopropanolamine, 2.6g of 3-amino-1,2-propanediol, and 0.5g of n-octadecylamine to the reactor, and stir for 24 hours until all components are fully mixed to obtain the oil phase system. The octadecyl alcohol polyoxyethylene ether in the oil phase has an HLB value of 12.5 and a weight-average molecular weight of 725.

[0045] 2. Preparation of aqueous system: Weigh 160g of silver nitrate and dissolve it in 320g of deionized water. Stir until completely dissolved to obtain the aqueous system.

[0046] 3. Microemulsion: Add the aqueous phase system to the reaction vessel containing the oil phase system, stir until a stable emulsion is formed, raise the temperature to 60℃, and react at a constant temperature for 8 hours.

[0047] 4. Post-processing: After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The product was then centrifuged and washed three times with anhydrous ethanol (each time using 10 times the volume of the mother liquor). After drying, silver nanoparticles were obtained. The SEM characterization results of the obtained product are shown below. Figure 1 As shown.

[0048] Example 2 The process is the same as in Example 1, except that 60g of octadecyl alcohol polyoxyethylene ether is replaced with 50g of dodecyl alcohol polyoxyethylene ether. The oil phase dodecyl alcohol polyoxyethylene ether has an HLB value of 14.5 and a weight-average molecular weight of 626.

[0049] Example 3 The process is the same as in Example 1, except that 2.6g of 3-amino-1,2-propanediol is replaced with 2.6g of 2-amino-1,3-propanediol.

[0050] Example 4 The process is the same as in Example 1, except that 2.6g of 3-amino-1,2-propanediol is replaced with 0.97g of triethylamine.

[0051] Example 5 The process is the same as in Example 1, except that 80g of isopropanolamine is replaced with 120g of diethanolamine.

[0052] Example 6 The process is the same as in Example 1, except that 0.5g of n-octadecylamine is replaced with 0.38g of n-dodecylamine.

[0053] Example 7 The process is the same as in Example 1, except that the temperature and reaction time are changed from 60°C for 8 hours to 50°C for 12 hours.

[0054] Comparative Example 1 The process is the same as in Example 1, except that it does not contain oil-phase octadecyl alcohol polyoxyethylene ether.

[0055] Comparative Example 2 The process is the same as in Example 1, except that it does not contain water.

[0056] Comparative Example 3 The process is the same as in Example 1, except that in step 3, the mixture is reacted directly without stirring until it reaches an emulsion state. The SEM characterization results of the obtained product are as follows: Figure 2 As shown.

[0057] Comparative Example 4 The process is the same as in Example 1, except that the oil phase is replaced with dehydrated sorbitan monostearate, i.e., Span 60, to form a water-in-oil system. The oil phase has an HLB value of 4.7 and a weight-average molecular weight of 430.

[0058] Comparative Example 5 The process is the same as in Example 1, except that the reaction temperature is controlled at 25°C.

[0059] Comparative Example 6 The process is the same as in Example 1, except that the reaction temperature is controlled at 95°C.

[0060] Test case The silver nanoparticles prepared by the processes in Examples 1-7 and Comparative Examples 1-6 were characterized and tested as follows: 1. Morphology and Particle Size Observation: 30g of wet nano-silver powder, which had been centrifuged and washed with anhydrous ethanol but was not yet dried, was baked at 60℃ for 10h to fully remove residual solvent, resulting in dried nano-silver powder (hereinafter referred to as "dry powder"). Approximately 0.1g of the dry powder was taken, and the morphology and microstructure of the particles were observed using a scanning electron microscope. The average particle size was also calculated.

[0061] 2. Loose packing density and tapped density test: Take about 15g of the above dry powder, accurately weigh its mass (accurate to 0.001g), pour it into a graduated cylinder, read the loose packing volume, and calculate the loose packing density. Then transfer the dry powder to a tapped density meter, set the vibration frequency to 3000 times and the amplitude to 3mm, read the tapped volume after the vibration is complete, and calculate the tapped density.

[0062] 3. Printing, Curing, and Conductivity Testing: Take another 10g of the washed but not yet dried wet powder and add 3.6g of diethylene glycol in three portions. After each addition, mix for 5 minutes using a centrifugal degassing machine at a vacuum of 0.5kPa and a speed of 1000rpm to ensure thorough and uniform dispersion of the components, thus preparing conductive ink. Apply this conductive ink to a 100mm long and 10mm wide linear pattern on a 100μm thick polyimide film and bake at 250℃ for 2 hours for thermosetting. After baking, allow it to cool naturally to room temperature. Measure the thickness of the cured conductive film using a mechanical contact thickness gauge and measure the sheet resistance (Ω / □) of the linear pattern using a four-probe resistance meter to evaluate the conductivity of the silver nanoparticles.

[0063] The specific representation structure is shown in Table 2.

[0064] Table 2

[0065] Based on the above test data, it can be seen that Examples 1-7 successfully prepared silver nanoparticles with an average particle size of less than 200 nm (34~155 nm). However, Comparative Examples 1-6, due to deviations from the technical solution of this application in terms of process conditions, failed to obtain qualified silver nanoparticles or could not obtain valid data. Among them, Example 1 used an oil phase octadecyl alcohol polyoxyethylene ether, surfactant n-octadecylamine, and a combination of primary and secondary reducing agents (isopropanolamine + 3-amino-1,2-propanediol), resulting in silver nanoparticles with an average particle size of only 65 nm, and both the loose packing density and tap density were at a high level (3.909 cm⁻¹, respectively). 3 / g and 5.511cm 3 The conductive film exhibits a sheet resistance as low as 0.136 Ω / □, demonstrating optimal overall performance. Examples 2-7, even with variations in oil phase type, reducing agent type, surfactant carbon chain length, or reaction conditions, still yielded silver nanoparticles in the 34-155 nm range with excellent conductivity (sheet resistance 0.161-0.383 Ω / □), fully validating the robustness and adjustability of the proposed technical solution. In contrast, Comparative Examples 1 (no oil phase), 2 (anhydrous), 4 (oil phase HLB value too low, forming a water-in-oil system), and 5-6 (reaction temperature too low or too high) failed to form stable oil-in-water microemulsions or achieve normal reactions, resulting in products with severe agglomeration, uncontrolled particle size, or almost no silver nanoparticles. Comparative Example 3 (not stirred to an emulsion state) also failed to form a uniform microemulsion, resulting in severe product agglomeration and deteriorated performance (loose packing density only 2.390 cm³). 3 / g, tap density is only 3.204cm³. 3 / g). The above comparative data fully demonstrate that the key technical guarantees for achieving the controllable particle size, good dispersion and high sintering activity of the silver nanoparticles described in this application are: the HLB value of the oil phase is in the range of 8 to 18, a stable oil-in-water (O / W) microemulsion structure is formed, the reaction temperature is controlled between 50℃ and 80℃, and the synergistic matching between the oil phase, surfactant and reducing agent.

Claims

1. A process for preparing silver nanoparticles smaller than 200 nm using a microemulsion method, characterized in that, Includes the following steps: An oil-phase system and an aqueous-phase system were prepared separately; the oil-phase system contained an oil phase, a surfactant, and a reducing agent; the aqueous-phase system contained a silver source and water. The oil phase system and the aqueous phase system are mixed and stirred to an emulsion state, and reacted at 50℃~80℃ to form an oil-in-water microemulsion. After post-processing and washing, nano-silver particles with a particle size of less than 200 nm were obtained; The oil phase is selected from at least one of polyethylene glycol monododecyl ether, polyethylene glycol monohexadecyl ether, polyethylene glycol mono(Z)-9-octadecenyl ether, polyethylene glycol monooctadecyl ether, hexanol polyoxyethylene ether, octyldecyl alcohol polyoxyethylene ether, n-octyl alcohol polyoxyethylene ether, dodecyl alcohol polyoxyethylene ether, tetradecyl alcohol polyoxyethylene ether, hexadecyl alcohol polyoxyethylene ether, octadecyl alcohol polyoxyethylene ether, coconut oil polyoxyethylene ether, polyethylene glycol monododecyl ester, polyethylene glycol monotetradecyl ester, polyethylene glycol monohexadecyl ester, polyethylene glycol mono(Z)-9-octadecenyl ester, polyethylene glycol monooctadecyl ester, and polyethylene glycol coconut oil ester, with a hydrophilic-lipophilic balance value of 8 to 18 and a weight-average molecular weight of 100 to 100,000; The surfactant is selected from at least one of methanol, ethanol, propanol, butanol, ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, glycerol, 1,2,3-butanetriol, 1,2,4-butanetriol, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, n-propylamine, dipropylamine, tripropylamine, 1,2-propanediamine, 1,3-propanediamine, propylenetriamine, n-butylamine, n-pentylamine, n-hexylamine, n-heptylamine, n-octylamine, n-nonylamine, n-decylamine, n-dodecylamine, n-tetradecylamine, n-hexadecylamine, n-octadecylamine, oleic acid amine, and linoleic acid amine; the reducing agent simultaneously comprises an alkanolamine compound and an amino polyol compound, with a molar ratio of 20:1 to 100:1; The alkanolamine compound is selected from at least one of methanolamine, ethanolamine, propanolamine, isopropanolamine, diethanolamine, triethanolamine, diisopropanolamine, triisopropanolamine, N-methylmethanolamine, N-methylethanolamine, N,N-dimethylethanolamine, N-ethylethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, N-acetylethanolamine, N-butyldiethanolamine, N-tert-butyldiethanolamine, and N,N-dimethylisopropanolamine. The amino polyol compound is selected from at least one of 3-amino-1,2-propanediol, 2-amino-1,3-propanediol, and 4-amino-1,2-butanediol.

2. The process according to claim 1, characterized in that, The oil phase is selected from at least one of dodecyl alcohol polyoxyethylene ether and octadecyl alcohol polyoxyethylene ether.

3. The process according to claim 1, characterized in that, The volume ratio of the oil phase system to the aqueous phase system is 0.01:1 to 10:

1.

4. The process according to claim 1, characterized in that, The surfactant is selected from at least one of n-dodecylamine and n-octadecylamine.

5. The process according to claim 1, characterized in that, The concentration of the surfactant is 0.01 g / L to 100 g / L.

6. The process according to claim 1, characterized in that, The alkanolamine compound is isopropanolamine; the amino polyol compound is selected from at least one of 3-amino-1,2-propanediol and 2-amino-1,3-propanediol.

7. The process according to claim 1, characterized in that, The molar ratio of the reducing agent to the silver source is 0.5:1 to 10:

1.

8. The process according to claim 1, characterized in that, The silver source is selected from at least one of silver nitrate, silver sulfate, silver chloride, silver oxide, silver trifluoroacetate, silver formate, silver acetate, silver oxalate, and silver carbonate. In the aqueous system, the mass ratio of silver source to water is 1:1000 to 1:1.

Citation Information

Patent Citations

  • Preparation method of silver powder with pore structures in spherical particles

    CN118385602A

  • High concentration metal particulate-dispersed liquid and its production method

    JP2006097116A